Modification Of Impact Testing Tools For Research Of Aluminum Alloys Energy Absorption Profile - Riyanta, Bambang; Nugroho, Hary; Rahman, Budi Nur (Universitas Muhammadiyah Yogyakarta, 2024)
One of the most popular materials used in industry is aluminum and its alloys. The aluminum manufacturing process is likely to undergo a welding process. Aluminum can be welded by gas or arc welding, but arc welding is more satisfactory. The welding process on aluminum alloys has the potential to present a situation similar to Age hardening. This research was conducted to dig deeper into the impact of welding on the second phase strengthening mechanism in several series of aluminum alloys using impact test equipment with the addition of a modified digital instrumentation device. Modifications were made to the GOTECH impact test equipment model Charpy impact test 0027 by changing the pendulum and adding a plate to the holder to conform to the ASTM E23-02a standard and adding digital instrumentation tools, including load cells, amplifiers, data acquisition, and power supply. The specimens used were aluminum 5052 and 6061 with variations of base metal and TIG welded V 60°. The results of the modified impact test equipment can display a graph of the impact energy absorption of each specimen. Comparison between the manual calculation of absorbed impact energy and digital calculation of 5052 base metal aluminum specimens has an average deviation of 11,716 J, 5052 welded specimens have an average deviation of 1.341 J, 6061 base metal specimens have an average deviation of 0.729 J, and 6061 welded specimens has a mean of 0.845 J.